PEMANFAATAN TEKNOLOGI VOICE OVER INTERNET PROTOCOL (VoIP) DALAM ONLINE MOBILE GAMES - Hanindar, Muthia; Irwansyah, Irwansyah (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2021)
Technological advancements have enabled progress in the video games industry. The emergence of mobile devices with increasingly sophisticated features allows audiences to play games anywhere and anytime. There is free time that needs to be filled as one of the main reasons for the audience to play games on their smart phones. The quality of smart phones that are increasingly being improved makes the world of the gaming industry more developed with the presence of new features in the game, one of which is the communication feature. Communication is very important especially in games that require teamwork. Voice over Internet Protocol (VoIP) technology allows this communication to occur. By using qualitative methods, this study aims to look at the needs of the audience that can be satisfied through the media consumed. Through the Uses and Gratifications 2.0 theory, it was found that someone's need can appear before consuming the media or appear after exploring the use of the media. Keywords: games, smart phones, communication, VoIP, uses and gratifications 2.0